Willingness and motives of domestic tourists to engage in community-based tourism (CBT) in Donsol, Sorsogon in the new normal - Atendido, Rachelle; Combalicer, Jermaine;Nuza, Janikka Mhae;Smith, Jason Tyler ;Zabala, Erika May (Manila : National University, 2022)
The tourism industry was adversely affected by the COVID-19 pandemic and the impact has been greatly felt in in community-based tourism.
Chapter 1. Introduction -- Chapter 2. Review of related literature and studies -- Chapter 3. Methodology -- Chapter 4. Results and discussion -- Chapter 5. Summary, Conclusion and recommendation -- References -- Appendices.
Includes bibliographical references.